The reaction of cell factors of swine's organism immunobiological defense at mixed nematodosis - S. I. Ponomar (Российский паразитологический журнал, 2016)
On pigs, experimentally infected by eggs Ascaris suum, Trichocephalus suis in a doze of respectively 500 and 200 eggs/kg of body weight, Oesophagostomum dentatum in a doze of 900 larva/kg and Strongyloides ransomi in a doze of 40 thousand of larva studied the dynamics cell factors of swine's organism immunobiological defense at mixed nematodosis comparatively with strongyloidosis monoinfection. It is established that the development of the pathological process at mixed nematodosis is accompanied by leucocytosis, eosinofilia, decreased number of erhythrocytes, lymphocytes and immunocompetent cells of T- and B-population, oppression of the helper and activation of the suppressor element of immune system, suppression of the receptor apparatus of the immunocompetent cells, decreased level of the mature T-lymphocytes and their functional activity.